2010
DOI: 10.1111/j.1749-8198.2010.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Climate Models for Hydrological Impact Studies at the Catchment Scale: A Review of Recent Modeling Strategies

Abstract: This article reviews recent applications of regional climate model (RCM) output for hydrological impact studies. Traditionally, simulations of global climate models (GCMs) have been the basis of impact studies in hydrology. Progress in regional climate modeling has recently made the use of RCM data more attractive, although the application of RCM simulations is challenging due to often considerable biases. The main modeling strategies used in recent studies can be classified into (i) very simple constructed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
227
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(235 citation statements)
references
References 80 publications
3
227
0
5
Order By: Relevance
“…As such, these cold regions are potentially more sensitive to future changes in climate. This is consistent with local (Lyon et al 2010) to regionalscale simulations (Teutschbein and Seibert 2010). In addition, GCMs tend to diverge in these regions in their ability to project similar changes in future climates.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 81%
“…As such, these cold regions are potentially more sensitive to future changes in climate. This is consistent with local (Lyon et al 2010) to regionalscale simulations (Teutschbein and Seibert 2010). In addition, GCMs tend to diverge in these regions in their ability to project similar changes in future climates.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 81%
“…2008; van Pelt et al, 2009;Driessen et al, 2010). Authors have used perturbed meteorological data from different GCM/RCM combinations under different SRES scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In their review of recent modeling strategies, Teutschbein and Seibert (2010) emphasized how hydrological modeling has focused on future climate uncertainty. They showed that multi-GCM/RCM approaches are more useful for climate change impact assessments than a single RCM.…”
Section: Introductionmentioning
confidence: 99%
“…However, there remain a number of challenges in producing precipitation projections that are optimal for climate impact studies of flooding (Teutschbein and Seibert, 2010;Beven, 2011). RCMs have a relatively higher resolution than GCMs (∌25 km compared to >200 km) while retaining the physical process representation of the climate.…”
Section: Introductionmentioning
confidence: 99%